The thermometer of sporting nationalism - Trivino, José Luis Pérez; Candalija, Rafael Valencia (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The connection between sport and nationalism is unquestionable. However, it is a matter of debate whether and to what extent this should be the case, given the potential danger involved. Cases of chauvinist exacerbation and even violence are well known. From a normative philosophical approach, we start with the hypothesis of a thermometer of sports nationalism that allows us to evaluate when these expressions are tolerable or not.
Keywords: nationalism; sport; violence; aggression